Adaptação, aclimatação e desenvolvimento do pirarucu (Arapaima gigas) em criação intensiva (Veterinária Notícias, 2014)
Adaptação, aclimatação e desenvolvimento do pirarucu (Arapaima gigas) em criação intensiva